(untitled) (Bangladesh Journal of Medical Science, 2022)
Background: Hemodialysis is an effective treatment carried out for patientswith chronic kidney failure to improve the quality of life. 80% of hemodialysis patients experience physical stress disorder and psychosocial stress related to treatment. When faced with stress, the body muscles become tense as the abdomen becomes tense and cramped, the chest feels tight, which impacts physical and psychosocial health, so it is necessary to have stress management training through relaxation techniques. This study aimed to determine the effect of progressive relaxation on stress levels in patients with hemodialysis. Method: A quasi-experimental pre-test and posttest study with control group design was used in this study. is a quasi-experimental pre-test and post-test study with a control group design. There were 58 respondents divided into two groups (intervention and control), and each group consisted of 29 people selected by random sampling. Measurement of stress levels using questionnaire Depression Anxiety Stress Scale 42 (DASS 42). Results: The Mann Whitney U Test showed a difference in the decrease instress levels which was statistically significant (p <0.05). Conclusion: The audio-visual progressive relaxation training conducted at least two times a week for three weeks effectively reduces stress levels in patients undergoing hemodialysis therapy for at least one month. Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 842-847